Estimation of dietary copper requirements of Coho salmon Oncorhynchus kisutch (Walbaum, 1792), and effects on the growth performance, tissue Cu content, antioxidant capacity and hematological parameters - Hairui Yu; Lingyao Li; Leyong Yu; Yujing Yao; Ling Zhang (Scientific Reports)
Abstract Copper (Cu) is an essential trace mineral for the growth of most farmed fish species. Since natural water typically contains low Cu levels, exogenous Cu supplementation may be required in intensive aquaculture systems to meet the nutritional requirements of certain fish species. A 10-week feeding experiment was conducted to evaluate the Cu requirement on growth performance, tissue Cu content, hematological parameters and anti-oxidant responses in coho salmon Oncorhynchus kisutch (Walbaum, 1792). In this experiment, six experimental diets supplemented with graded Cu (CuSO4 used as Cu source) contents (0.20, 2.10, 3.70, 5.80, 7.75, and 9.85 mg/kg) to feed the fish (180.22 ± 0.41 g). Total 180 fish were randomly distributed across 18 individuals tank (10 fish/cage, water volume 1,000-L) fed three times a day. The result showed that the mortality and morphological indices were completely unaffected by the increasing Cu supplementation in the diet (P > 0.05). Whereas, the non-supplemented diet (0.20 mg Cu/kg) had a poor growth performance of the fish (P < 0.05), including the lowest final body weight and specific growth rate, the highest feed conversion ratio. No significant differences (P > 0.05) were observed in the proximate composition of muscle across graded dietary copper levels. However, increasing dietary Cu level induced Cu accumulation (P < 0.05), but higher Cu level in the diet (> 5.8 mg/kg) did not further increase of muscle and liver in coho salmon. Compared with the 0.20 Cu mg/kg in diet, the supplemented diet enhanced the antioxidant capacity in liver and serum, and decrease the content of malondialdehyde in liver (P < 0.05). Diet with 0.20-5.80 mg/kg supplemental Cu significantly increased the serum alkaline phosphatase and lysozyme activities, decrease the serum alanine aminotransferase and aspartate aminotransferase activities (P < 0.05), while higher dietary Cu level (> 5.8 mg/kg) showed the opposite trend. The broken-line analysis based on specific growth rate, liver Cu accumulation, copper-zinc superoxide dismutase in liver and serum, the appropriate dietary Cu level for coho salmon were estimated to be 5.29–5.92 mg/kg.